Endoscopic Endonasal Supraoptic and Infraoptic Approaches for Complex “Parasuprasellar” Lesions: Surgical Anatomy, Technique Nuances, and Case Series - Bao, YouYuan; Yang, YouQing; Zhou, Lin; Xie, ShenHao; Wu, Xiao; Ding, Han; Wu, Jie; Xiao, Limin; Yang, Le; Tang, Bin; Hong, Tao (Frontiers in Oncology, 2022)
Objective: The surgical management of lesions involving the lateral area of the suprasellar region, including the lateral aspect of the planum sphenoidale and the tight junction region of the optic canal (OC), anterior clinoid process (ACP), and internal carotid artery (ICA) and its dural rings, is extremely challenging. Here, these regions, namely, the “parasuprasellar” area, are described from the endonasal perspective. Moreover, the authors introduce two novels endoscopic endonasal supraoptic (EESO) and endoscopic endonasal infraoptic (EEIO) approaches to access the parasuprasellar area. Methods: Surgical simulation of the EESO and EEIO approaches to the parasuprasellar area was conducted in 5 silicon-injected specimens. The same techniques were applied in 12 patients with lesions involving the parasuprasellar area. Results: The EESO approach provided excellent surgical access to the lateral region of the planum sphenoidale, which corresponds to the orbital gyrus of the frontal lobe. With stepwise bone (OC, optic strut and ACP) removal, dissociation of the ophthalmic artery (OA) and optic nerve (ON), the EEIO approach enables access to the lateral region of the supraclinoidal ICA. These approaches can be used independently or in combination, but are more often employed as a complement to the endoscopic endonasal midline and transcavernous approaches. In clinical application, the EESO and EEIO approaches were successfully performed in 12 patients harboring tumors as well as multiple aneurysms involving the parasuprasellar area. Gross total and subtotal tumor resection were achieved in 9 patients and 1 patient, respectively. For two patients with multiple aneurysms, the lesions were clipped selectively according to location and size. Visual acuity improved in 7 patients, remained stable in 4, and deteriorated in only 1. No postoperative intracranial infection or ICA injury occurred in this series. Conclusions: The EESO and EEIO approaches offer original treatment options for well-selected lesions involving the parasuprasellar area. They can be combined with the endoscopic endonasal midline and transcavernous approaches to remove extensive pathologies involving the intrasellar, suprasellar, sphenoid, and cavernous sinuses and even the bifurcation of the ICA. This work for the first time pushes the boundary of the endoscopic endonasal approach lateral to the supraclinoidal ICA and ON.